Evaluasi kualitas pelayanan akta kelahiran berbasis digital di dinas kependudukan dan pencatatan sipil kota tomohon - Astrid Maria Tuerah; Audya Dewintha; Nimas Hapsari; Giovani Naharia (Jurnal Pengetahuan dan Pendidikan, 2026)
Evaluating Digital-Based Birth Certificate Service Quality at the Population and Civil Registration Office of Tomohon City. Digital-based birth certificate services represent a concrete manifestation of bureaucratic transformation anchored in information technology. However, the success of this transformation cannot be measured solely by the availability of digital infrastructure; it must be critically evaluated from the perspective of real user experience. This study aims to evaluate the quality of birth certificate services at the Population and Civil Registration Office of Tomohon City in the post-pandemic period (July–December 2025), using three dimensions of the ServQual model operationalized in the digital public service context: tangible, reliability, and responsiveness. A descriptive-evaluative qualitative approach was employed with data collected through in-depth interviews, observation, and documentation. The evaluation results reveal that despite the end of the pandemic and the full operation of the e-Dukcapil system, the gap between technological capacity and human resource readiness as well as community digital literacy remains a persistent structural barrier. The novelty of this study lies in its analysis of the technology-readiness gap in civil registration services in the post-pandemic era in a high-HDI region, which paradoxically still faces a digital service quality deficit.